Assessing factors associated with changes in the numbers of birds visiting gardens in winter: Are predators partly to blame?. Issue 21 (11th October 2019) - Swallow, Ben; Buckland, Stephen T.; King, Ruth; Toms, Mike P.
Abstract: The factors governing the recent declines observed in many songbirds have received much research interest, in particular whether increases of avian predators have had a negative effect on any of their prey species. In addition, further discussion has centered on whether or not the choice of model formulation has an effect on model inference. The study goal was to evaluate changes in the number of 10 songbird species in relation to a suite of environmental covariates, testing for any evidence in support of a predator effect using multiple model formulations to check for consistency in the results. We compare two different approaches to the analysis of long‐term garden bird monitoring data. The first approach models change in the prey species between 1970 and 2005 as a function of environmental covariates, including the abundance of an avian predator, while the second uses a change–change approach. Significant negative relationships were found between Eurasian Sparrowhawk Accipiter nisus and three of the 10 species analyzed, namely house Sparrow Passer domesticus, starling Sturnus vulgaris, and blue tit Cyanistes caeruleus . The results were consistent under both modeling approaches. It is not clear if this is a direct negative impact on the overall populations of these species or a behavioral response of the prey species to avoid feeding stations frequented by Sparrowhawks (which may in turn have population consequences, by reducing available resources). The species showing evidence of negative effects of Sparrowhawks were three of the four species most at risk to Sparrowhawk predation according to their prevalence in the predator's diet. The associations could be causal in nature, although in practical terms the reduction in the rate of change in numbers visiting gardens accredited to Sparrowhawks is relatively small, and so unlikely to be the main driver of observed population declines. Abstract : We analyse data from the British Trust for Ornithology's Garden Bird Feeding Survey over a 40‐year period to determine what are the likely factors behind severe declines observed in some of the 10 species we focus on. In particular, we include abundance of Sparrowhawks, a known predator of small garden birds, to determine whether they could be a contributing factor in the declines. Our results show that they are likely to be contributing to the negative population change of their preferred prey species, although this contribution is minimal compared to other environmental factors.